Study of Myrsine capitellata wall in forest areas of Paiyunpata Village, Baglung, Nepal - Pathak, Hom Nath (International Journal of Environment, 2014)
Present study focuses on ecology of Myrsine capitellata Wall. and its rapid decline due to over-exploitation in forests of Paiyunpata Village, Baglung district. Ecological parameters like importance value, species diversity, etc. have been studied. Besides, soil characters and causes and consequences of its deforestation have been discussed. The Myrsine capitellata Wall. is important forest component of the study area. Community diversity is less in North facing slope than in south facing slope. Soil is acidic, with high WHC value, low moisture content and sandy type of texture. After this study, it is recommended to begin for the extensive plantation and other conservation efforts of Myrsine before being extinct. DOI: http://dx.doi.org/10.3126/ije.v3i2.10504 International Journal of the Environment Vol.3(2) 2014: 55-62